Anthropology & the colonial encounter - Asad, Talal (Humanity, 1973)
The papers in this book analyze and document ways in which anthropological thinking and practice have been affected by British colonialism. They approach this topic from different points of view and at different levels. Each stands as an original contribution to an argument which is only just beginning.